A Comparative Analysis of Super Nations’ Pre and Trade War Periods on Nigeria - Ebegbetale, Christopher Idemudia; Olayemi, Olufemi Olabode (Business and Entrepreneurial Review, 2023)
There is no contention that the contemporary world has been reduced to a global village but of great concern is how policies that were made in other distant economies affect other places’ economy, politics, culture, education, etc. This study primarily investigated whether US-China trade war had any impact on their trade with Nigeria. This is because the US and China are Nigeria’s important trading partner and it is expected that whatever happened in these two leading world economies would have impacts on other countries. The period Q12014-Q42019 was adopted for the study because it allowed the researcher to compare the performance of the Nigeria’s trade with the two countries before trade war with the performance during the trade war period. The pre-trade war period adopted for this study was Q12014 to Q42016 while the trade war period was Q12017 to Q42019. The study used secondary data from Nigeria’s export and import trade with US and China. All the data were quarterly data and obtained from the website of National Bureau of Statistics (NBS) quarterly bulletin. The study was delimited to export and import trade between Nigeria and US-China because trade tariff policies have significant impact on imports and exports and the effect is strongest on trade. The paired-samples t-test techniques were used to analyse the data. The findings revealed that there was a significant difference in Nigeria’s trade flow with the US and China during the trade war periods when compared to the periods before the trade war.